Table Tennis classes at Junior High Schools utilizing the TPACK-Based Problem-Based Learning Model - Siregar, Samsuddin; Hasibuan, Juli Rachmadani; Anggraini, Cindy; Marpaung, Aidil Arifin; Br Marbun, Yohana Dede (INSPIREE: Indonesian Sport Innovation Review, 2022)
The  purpose  of  the study. Through the application of the TPACK - based PBL model , it can improve learning outcomes in the aspect of table tennis service material skills for junior high school students. Materials and methods. The method used is the Action Research Class method with two cycles, each cycle through the stages of planning, action, observation and reflection. The research subjects were 25 students. The data of this research is the result of learning table tennis service and analyzed by using the percentage technique of Sugiyono's theory. Results. Student learning outcomes in the aspect of skills have increased from cycle one to cycle two. aspects of service learning outcomes at the implementation stage the percentage obtained in the first cycle was only 74.3%, an increase in the second cycle to 97.7%. Likewise, at the final stage of cycle one, it was only 35%. students who complete have increased in the second cycle to 81%. Conclusions. The TPACK-based learning problem model makes learning more meaningful and the learning outcomes of Junior High School students experience classical mastery.